2022
DOI: 10.30604/jika.v7is2.1423
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lavender essential oil aromatherapy on sleep quality in hemodialysis patients

Abstract: Hemodialysis is a long-term therapy that must be undertaken by patients with chronic kidney disease. Patients who undergoing therapy for a very long time will have an impact on the patient's psychology. One of the psychological effects that arise is sleep disorder. Poor sleep quality can lead to physiological changes, the endocrine system, the cardiovascular system, the immune and nervous systems. To overcome sleep disorder in hemodialysis patients, nonpharmacological options can be used, namely Lavender Essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…The score of each dimension of sleep quality after inhalation was significantly lower than before inhaling the essential oil. In other words, inhaling lavender essential oil improved sleep quality, including subjective sleep quality, sleep latency, sleep adequacy, sleep duration, and daily sleep dysfunction in hemodialysis patients (19). This study's results align with those of the present study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The score of each dimension of sleep quality after inhalation was significantly lower than before inhaling the essential oil. In other words, inhaling lavender essential oil improved sleep quality, including subjective sleep quality, sleep latency, sleep adequacy, sleep duration, and daily sleep dysfunction in hemodialysis patients (19). This study's results align with those of the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Numerous studies have examined the effects of lavender on anxiety, depression, stress, fatigue, and pain in patients undergoing hemodialysis and have reported positive results (7,17,18). Several studies have shown that aromatherapy with lavender essential oil can improve the sleep quality of patients undergoing maintenance hemodialysis (19,20). However, a study reported that aromatherapy with lavender essential oil had no significant effect on sleep quality in patients undergoing maintenance hemodialysis (21).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, George et al, [20] reported that severe anxiety level was found among HD patients. While Setyaningrum et al, [21] proved that the highest percent of HD patients was suffering from sleep problems. In addition, several studies show that better function of PMR in managing the symptoms associated with anxiety and sleep problem in patients with HD.…”
Section: Introductionmentioning
confidence: 97%